Preclinical evaluation of WVE-004, aninvestigational stereopure oligonucleotide forthe treatment of C9orf72-associated ALS or FTD - Yuanjing Liu; Amy Andreucci; Naoki Iwamoto; Yuan Yin; Hailin Yang; Fangjun Liu; Alexey Bulychev; Xiao Shelley Hu; Xuena Lin; Sarah Lamore; Saurabh Patil; Susovan Mohapatra; et al. (Molecular Therapy: Nucleic Acids, 2022)
A large hexanucleotide (G4C2) repeat expansion in the first intronic region of C9orf72 is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Several mechanisms have been proposed to explain how the repeat expansion drives disease, and we hypothesize that a variant-selective approach, in which transcripts affected by the repeat expansion are preferentially decreased, has the potential to address most of them. We report a stereopure antisense oligonucleotide, WVE-004, that executes this variant-selective mechanism of action. WVE-004 dose-dependently and selectively reduces repeat-containing transcripts in patient-derived motor neurons carrying a C9orf72-repeat expansion, as well as in the spinal cord and cortex of C9 BAC transgenic mice. In mice, selective transcript knockdown was accompanied by substantial decreases in dipeptide-repeat proteins, which are pathological biomarkers associated with the repeat expansion, and by preservation of healthy C9orf72 protein expression. These in vivo effects were durable, persisting for at least 6 months. These data support the advancement of WVE-004 as an investigational stereopure antisense oligonucleotide targeting C9orf72 for the treatment of C9orf72-associated ALS or FTD.